Transformasi Pendidikan Islam di Iran: Kajian atas Integrasi Nilai Keislaman dan Modernisasi Pendidikan - Oma Aprida; Lukman Asha; Fakhruddin Fakhruddin (Berkala Ilmiah Pendidikan, 2024)
The transformation of Islamic education in Iran represents a successful model of integrating Islamic values with modern knowledge. This study aims to analyze the Islamic value-based curriculum approach, the strategic roles of the government and ulama, and its implications for education quality. The method used is library research with a descriptive approach. The results indicate that Iran's curriculum achieves a balance between mastery of knowledge and spiritual reinforcement. Collaboration between the government and ulama provides a foundation for education modernization that remains consistent with Islamic teachings. This transformation has resulted in graduates who are globally competitive without losing their Islamic identity. This study recommends adapting Iran's educational approach in other Muslim countries with adjustments to local contexts.